2022
DOI: 10.3329/bjms.v21i4.60290
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of safety and efficacy of Unani Add-on regimen in preventing the progression of severity of the disease in hospitalized SARS-CoV2 tested positive asymptomatic /mild to moderate symptomatic COVID-19 cases- A Randomised Controlled Clinical Trial

Abstract: Objectives: The study aimed to establish the effectiveness of Unani add-on regimen by comparing theduration required for change in disease status from COVID-19 positive asymptomatic / mildto moderate symptomatic patients to asymptomatic negative. Methods: This single-centric, randomized, twin arm, controlled, clinical trial was carried out on a totalnumber of 62 RT-PCR confirmed COVID-19 patients. The Intervention group (IG) receivedUnani Regimen (Khameera Marwareed and Unani Joshanda) in addition to the conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…We found that patients who received combination therapy (add-on Unani treatment along with standard treatment) in the intervention arm got early discharge and spent comparatively lesser days in the hospital in contrast to the control arm. Decreased length of stay has been associated with decreased risks of iatrogenic infections, fewer side effects of medication, and reduced unnecessary burden of medical cost on patients, and also helps reduce the patient load on the already overwhelmed health care system, as was observed during the second wave of the pandemic in India [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that patients who received combination therapy (add-on Unani treatment along with standard treatment) in the intervention arm got early discharge and spent comparatively lesser days in the hospital in contrast to the control arm. Decreased length of stay has been associated with decreased risks of iatrogenic infections, fewer side effects of medication, and reduced unnecessary burden of medical cost on patients, and also helps reduce the patient load on the already overwhelmed health care system, as was observed during the second wave of the pandemic in India [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The addition Siddha formulations with the standard treatment exhibit early clinical recovery without further progression in mild to moderate COVID-19 cases [ 30 ]. A similar study with Unani formulations having similar decoction ( Joshanda ) as an add-on with standard treatment showed accelerated recovery for COVID-19 patients compared to the standard Group [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of these medicines has beneficial effects in improving the immunity of an individual as well as early recovery of mild to moderate COVID-19 confirmed cases. 10,12 India is considered to be the third world's worst-affected country in the COVID-19 pandemic. Sudden lockdown isolation, curfew, social distancing, and precautionary measures had strongly impacted people's life by affecting their lifestyle, eating habits, sleep routine, and physical activity.…”
Section: Increase In Traditional Medicine and Other Supplementationmentioning
confidence: 99%